Assessment of the Reproductive Health Status of Adult Prison Inmates in Osun State, Nigeria - Olugbenga-Bello, A. I.; Adeoye, O. A.; Osagbemi, K. G. (International Journal of Reproductive Medicine, 2013)
Introduction. All over the world, numbers of prisoners have being increasing with majority in the sexually active age group; hence diseases such as HIV, Tuberculosis and Hepatitis are more prevalent in prisons than in the community. This study thus aims to provide an overview of the reproductive health status of adult prison inmates in Osun State. Methodology. This is a cross-sectional study among adult inmates in Osun State prison. Data was obtained from 209 selected respondents using pre-tested semi structured questionnaire. Result. Majority of the respondents were in the age group 20–39 years with mean age of 30.9+7.5. 73.2% are aware of STIs, 93.3% HIV/AIDS and 81.3% contraception. 54.6% had multiple sexual partners before incarceration and 23.3% of them used condom always. 89.5% were not involved in any sexual practice inside the prison, 9.1% masturbated and 1.4% had homosexual partners. Less than 6% had access to male condoms gotten from prison staffs and prison clinics. Conclusion and recommendation. No comprehensive reproductive health care system to address reproductive health services in prisons. Respondents’ knowledge about STIs, HIV/AIDS and contraception is good, but their condom usage is low compared with the knowledge. Government should put in place specific reproductive health programmes in prisons.